Mediating Effect of Customer Satisfaction on Service Quality and Customer Loyalty Relationship in Malaysian Rural Tourism - Osman, Zahir; Sentosa, Ilham (International Journal of Economics, Business and Management Studies, 2013)
The aim of this study is to develop an indirect effect of understanding service quality, customer satisfaction and customer loyalty in Malaysia rural tourism. The model was designed and later examined by utilizing the Partial Least Square (PLS) procedure on data collected from a survey that yielded 295 usable questionnaires. The results confirmed that customer satisfaction have significant and positive partial mediating effect on service quality and customer loyalty relationship in Malaysia rural tourism. It is vital to do the study utilizing experimental design by capturing longitudinal data in Malaysia rural tourism industry using robust measures. The findings imply that the relationship of service quality, satisfaction and customer loyalty will lead to rural tourism operators? profitability. Therefore service quality and customer satisfaction play a crucial function within the Malaysia rural tourism industry. This research is one of the first known attempts to use PLS to test a mediation effect.